2017
DOI: 10.1021/acs.biochem.7b00141
|View full text |Cite
|
Sign up to set email alerts
|

Structure of RNA Stem Loop B from the Picornavirus Replication Platform

Abstract: The presumptive RNA cloverleaf at the start of the 5′-untranslated region of the picornavirus genome is an essential element in replication. Stem loop B (SLB) of the cloverleaf is a recognition site for the host polyC-binding protein, which initiates a switch from translation to replication. Here we present the solution structure of human rhinovirus isotype 14 SLB using nuclear magnetic resonance spectroscopy. SLB adopts a predominantly A-form helical structure. The stem contains five Watson–Crick base pairs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…The imino chemical shift difference between SLB and SLD in previously described isolated stem-loops (Headey et al 2007;Warden et al 2017) versus when incorporated into the 5 ′ CL (without magnesium) are shown in Figure 3A. The differences are small (RMSD 0.028 ppm), FIGURE 1.…”
Section: Chemical Shift Changes Upon Incorporation Into Cloverleafmentioning
confidence: 90%
See 4 more Smart Citations
“…The imino chemical shift difference between SLB and SLD in previously described isolated stem-loops (Headey et al 2007;Warden et al 2017) versus when incorporated into the 5 ′ CL (without magnesium) are shown in Figure 3A. The differences are small (RMSD 0.028 ppm), FIGURE 1.…”
Section: Chemical Shift Changes Upon Incorporation Into Cloverleafmentioning
confidence: 90%
“…In this overlay, part of the SLB loop region extends outside of the ab initio model. However, this SLB loop has been shown to be highly dynamic (Warden et al 2017), and so its position in this figure is somewhat misleading. As a dynamic loop, it can explore many conformations and positions, and so may not give rise to intense density in the ab initio model.…”
Section: Comparison Of Saxs-only Models With Saxs/nmrbased Structuresmentioning
confidence: 97%
See 3 more Smart Citations